Second Law Of Thermodynamics Analysis Of Triple Cycle Power Plant - Matheus M. Dwinanto (Jurnal Energi Dan Manufaktur, 2010)
Triple cycle power plant with methane as a fuel has been analyzed on the basis of second law of thermodynamics.In this model, ideal Brayton cycle is selected as a topping cycle as it gives higher efficiency at lower pressure ratio comparedintercooler and reheat cycle. In trilple cycle the bottoming cycles are steam Rankine and organic Rankine cycle. Ammoniahas suitable working properties like critical temperature, boiling temperature, etc. Steam cycle consists of a deaerator andreheater. The bottoming ammonia cycle is a ideal Rankine cycle. Single pressure heat recovery steam and ammoniagenerators are selected for simplification of the analysis. The effects of pressure ratio and maximum temperature which aretaken as important parameters regarding the triple cycle are discussed on performance and exergetic losses. On the otherhand, the efficiency of the triple cycle can be raised, especially in the application of recovering low enthalpy content wasteheat. Therefore, by properly combining with a steam Rankine cycle, the ammonia Rankine cycle is expected to efficientlyutilize residual yet available energy to an optimal extent. The arrangement of multiple cycles is compared with combinedcycle having the same sink conditions. The parallel type of arrangement of bottoming cycle is selected due to increasedperformance.